The acceptability of blood spot screening and genome sequencing in newborn screening: a systematic review examining evidence and frameworks - Duncan Chambers; Susan Baxter; Anastasios Bastounis; Katherine Jones; Burak Kundakci; Anna Cantrell; Andrew Booth (Health Technology Assessment)
Background Population-wide newborn blood spot screening programmes are a successful public health intervention used to detect whether the baby is at risk of certain rare conditions, with the aim of earlier diagnosis and provision of optimal care and treatment. Evaluating candidate conditions to include in newborn blood spot and genetic sequencing raises questions regarding acceptability to parents/carers. Methods In the context of the possible expansion of the newborn blood spot screening programme in the United Kingdom, this review aimed to systematically review research on the acceptability to parents of newborn blood spot screening and genetic sequencing. A protocol was developed prior to commencing the review and was registered on the PROSPERO database. A team of researchers carried out the review, with checking at all stages carried out by at least two individuals. We included research published after 2013 with participants who were pregnant or a recent parent of a newborn and were resident in a high-income country. We included quantitative and qualitative studies that investigated the acceptability to parents/carers of newborn blood spot screening or genetic sequencing. Quantitative studies were narratively synthesised, and theories/frameworks identified and evaluated. Qualitative studies were analysed for recurring themes, and a meta-synthesis was carried out to compare and contrast these two types of data. We quality appraised included articles using tools appropriate for their study design. Results Searches were carried out in September to November 2023 and screening identified 25 relevant research articles. Just over half were from North America, with four existing reviews and nine qualitative studies. Domains of acceptability described in the literature were: support for screening; level of anxiety, information and knowledge; consent; views of the procedure; and support after screening. The research indicated consensus support for blood spot screening, and for expanding to some other conditions, although some parental anxiety was reported. Parents/carers mostly perceived that they had received sufficient information, but the timing of this could be improved. While parents indicated interest in genomic screening, studies highlighted the need for clearer consent procedures and greater support for parents following genomic screening than for blood spot screening. Only three included studies reported using any kind of theoretical framework. Discussion Most parents/carers found newborn blood spot screening programmes to be acceptable and favoured their large-scale implementation. A minority of parents/carers expressed concerns regarding the acceptability of processes underpinning newborn blood spot screening, such as consent, the timing of receiving information and support available after testing. More research is needed regarding the acceptability of newborn genomic sequencing screening programmes, which are less established compared with newborn blood spot screening programmes. Limitations The over-representation of studies conducted in the United States has implications for the applicability of findings to other countries where testing is not typically mandatory and health systems differ considerably. Most studies were of cross-sectional design and there was limited representation of people from lower incomes and non-white ethnicity. While the inclusion of studies only in populations of future or very recent parents provided coherence to the findings, unclear reporting of participants may have resulted in under- or overinclusion of some studies. Funding This article presents independent research funded by the National Institute for Health and Care Research (NIHR) Health Technology Assessment programme as award number NIHR159927. Plain language summary Blood spot screening in newborns typically involves taking and testing a spot of blood from a baby’s heel soon after birth (often called the heel-prick test). It aims to find out if a baby might be at risk of or already have certain rare conditions. Finding out means that care and treatment can be provided as early as possible. Over the years more conditions have been added to the list screened for. New technology means that gene/DNA testing could be used to find out about other diseases. We brought together recent research on parent views of the acceptability of screening. Including what is done now and what might be done in the future. We looked at research with parents/carers of a newborn living in countries like the United Kingdom. We found 25 relevant research articles. Just over half were carried out in North America. Most parents/carers supported newborn screening. They also supported adding more conditions to the list. There was interest in gene/DNA screening, but parents/carers wanted clear permission procedures beforehand and enough support afterwards. Most parents/carers said they had received enough information but some said the timing could have been better. The review found that blood spot screening and gene/DNA newborn screening are generally acceptable to parents but much of the research comes from the United States, where the healthcare system and permission process are very different from the United Kingdom. Researchers said that acceptability of newborn screening to parents/carers means: providing enough information at the right time knowing what you are giving permission for having time to weigh up pros and cons being given results in the right way by the right person being able to trust the healthcare system. Decisions about new types of newborn screening need to take into account these important features of acceptability to parents/carers.